(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article analyzes the architectural features and preservation status of traditional residential buildings located in the historical center of Bukhara. Using examples from Mehtar Ambar, Arabon, and Khoja Nurobod Streets, the study examines spatial layouts, decorative elements, functional zones, and restoration status. Dwellings from the late 19th and early 20th centuries are evaluated through the lens of traditional Bukhara architecture, including carved plaster, niches, and courtyard-based layouts. The research offers recommendations for preserving this heritage within the context of modern urban development.